Strength and stiffness assessment of an LNG containment system – Crushing and buckling failure analysis of plywood components. (February 2015) - Arswendy, A.; Moan, Torgeir
Highlights: LNG containment system No. 96. Plywood. Crushing analysis. Buckling analysis. FE analysis and material tests. Abstract: A liquefied natural gas (LNG) containment system (LCS) No. 96 type is built up as a box system consisting of plywood plates and bulkheads. Plywood components are connected using staple connectors. The aim of this paper is to explain the crushing and buckling failure of plywood component of an LCS No. 96. A systematic study of crushing and buckling behavior of plywood components is conducted by means of experiments and finite element (FE) analysis. The FE study is based on numerical material modeling using Hashin's theory and fracture energy approach as damage initiation and evolution, respectively. Observations on strength and progressive deformation during the crushing and buckling tests are discussed. It is observed that crushing failure of plywood bulkheads determines the ultimate crushing capacity. Crushing failure of plywood plate which is due to shear through the thickness failure of the veneer, causes reduced stiffness before the ultimate crushing capacity is reached. It is found from buckling test that staple connectors have no influence on structural strength nor stiffness, i.e. they keep the structure together during manufacturing. During buckling of bulkheads, withdrawal of staple legs from the plywood bulkhead is observed. Thus, plywood bulkheads are supported on their edges and creates hinge like support. The numerical simulations – including the use of the damage model of plywood components – agree well with the test results.